The Effect of Perceived Usefulness on Digital Technology Adoption among MSME Owners in Tasikmalaya City - Manurung, Rosita Marta Valensya; Kurnia, Dede; Yusup, Ismail (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The development of the digital economy encourages Micro, Small, & Medium Enterprises (MSMEs) to adopt digital technology in their business activities. However, digital technology adoption among MSMEs remains uneven because some business owners still do not perceive clear benefits from using technology. This study aims to describe Perceived Usefulness & Digital Technology Adoption & to analyze the effect of Perceived Usefulness on Digital Technology Adoption among MSME owners in Tasikmalaya City. This study used a quantitative method with a descriptive-verificative approach. Data were collected through a structured questionnaire using a five-point Likert scale. The sample consisted of 384 MSME owners in Tasikmalaya City who had used or had begun to use digital technology in their business activities. Data were analyzed using descriptive analysis, classical assumption tests, simple linear regression, bootstrap, HC3, coefficient of determination, & t-test. The results show that Perceived Usefulness & Digital Technology Adoption are in the high category. Perceived Usefulness has a positive & significant effect on Digital Technology Adoption, with a regression coefficient of 0.768, t-value of 10.339, p < 0.001, & R² of 0.637. These findings indicate that the higher the perceived benefits of digital technology, the higher the level of digital technology adoption among MSME owners. This study suggests that benefit-oriented digital literacy & practical technology assistance should be strengthened.